The Influence of Attractions and Amenities on Revisit Intention at the Natural Tourism Object of the Hulu Dayeuh Trijaya Campground, Mandirancan District, Kuningan Regency - Rizqi Annisha; Hotimah, Oot; Munandar, Aris (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2022)
The Natural Tourism Object of the Hulu Dayeuh Trijaya Campground is a natural tourism object managed by the community and is an icon of Trijaya Village, Kuningan Regency. This tourist attraction was opened to the public in 2016 with problems related to the number of visits that fluctuated, which affected the village’s original income and the community welfare of Trijaya Village. This research aims to examine and analyze the influence of attractions and amenities on revisit intention at the Natural Tourism Object of the Hulu Dayeuh Trijaya Campground. The method used in this research is the quantitative descriptive approach processed using multiple linear regression analysis. The data collection technique was obtained by distributing questionnaires to 100 tourists at the research site. Based on the research results, the partial attractions variable and amenities variable significantly affect to revisit intention of tourists to the Natural Tourism Object of the Hulu Dayeuh Trijaya Campground. By proving the value of sig. <0.05 and the value of tcount > ttable, then H0 is rejected and Ha is accepted.